Different rootstocks affect yield and fruit quality of ‘Forastero’ peach - Arroyo, Luis Enrique (2006)
Selecting peach rootstocks suitable to the fruit growing area in the northeastern Buenos Aires Province (Argentina) was the research objective. The effects of rootstocks (‘Cuaresmillo’ seedling, ‘Ferdor Julior’ (FJ), ‘Mr.S 2/5’ and ‘GF 655/2’, both cutting and in vitro propagated) on ‘Forastero’ peach culivar were evaluated. Tree vigor, productivity and fruit quality were affected by the rootstock. ‘Cuaresmillo’ and ‘FJ’ induced the highest vigor. The highest yield and production efficiency was obtained with ‘Cuaresmillo’, which significantly differed from the other treatments. As to fruit quality, ‘Forastero/Cuaresmillo’ was significantly different from the other cultivar/rootstock combinations. Fruits with higher flesh firmness, and lower SSC were observed on ‘Forastero/Cuaresmillo’ and were significantly different from the other cultivar/rootstock combinations.